Observational effect of Chitin and Chitosan from Horseshoe crab’s exoskeleton on the test animal, zebrafish Danio Rerio, under the laboratory condition - Wan Omar, Wan Syazzawani; Sulaiman, Wan Mohd Azizi Wan; Kassim, Zaleha; Elgharbawy, Amal A. M. (Medwin Publishers, 2022)
Being a component of crustacean’s exoskeleton, chitin is one of main carbohydrate found on earth. Its derivative, chitosan can be isolated through deacetylation process of chitin. Due to their potential in pharmaceutical field, this study is using chitin and chitosan isolated from horseshoe crab to be tested on zebrafish (Danio rerio) developing embryo at various volumes. By using Danioscope, morphological defects on zebrafish embryos and larvae has been observed. We found out that both chitin and chitosan affect the zebrafish in several morphological abnormalities including dented tail, accumulation of blood, stunted development, enema and no pigmentation observed. Percentage of mortality was also determined for three different concentrations of chitin and chitosan which are at 10µl, 50µl and 100µl that been exposed to the embryo. Chitosan shows higher mortality rate compared to chitin. Both observations and data on morphological defects and mortality rate help in determining the toxicity level of chitin and chitosan on zebrafish and their effects. Our results suggested that both compounds are toxic at certain amount, hence having a high capability to be used in combating pathogens and tumour.